Application of swarm robotics systems to marine environmental monitoring - Duarte, M. (2018)
Automated environmental monitoring in marine environments is currently carried out either by small-scale robotic systems, composed of one or few robots, or static sensor networks. In this paper, we propose the use of swarm robotics systems to carry out marine environmental monitoring missions. In swarm robotics systems, each individual unit is relatively simple and inexpensive. The robots rely on decentralized control and local communication, allowing the swarm to scale to hundreds of units and to cover large areas. We study the application of a swarm of aquatic robots to environmental monitoring tasks. In the first part of the study, we synthesize swarm control for a temperature monitoring mission and validate our results with a real swarm robotics system. Then, we conduct a simulation-based evaluation of the robots' performance over large areas and with large swarm sizes, and demonstrate the swarm's robustness to faults. Our results show that swarm robotics systems are suited for environmental monitoring tasks by efficiently covering a target area, allowing for redundancy in the data collection process, and tolerating individual robot faults.